2012
DOI: 10.1155/2012/241816
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-Like Carcinoma of the Skin Treated with Wide Local Excision and Chemoradiation Therapy: A Case Report and Review of the Literature

Abstract: Lymphoepithelioma-like carcinoma of the skin (LELCS) is a rare cutaneous neoplasm microscopically similar to undifferentiated nasopharyngeal carcinoma. It is typically nonaggressive and is treated with wide local excision. However, we present a case of a patient with a regional recurrence and more aggressive LELCS with perineural invasion and positive margins for which he was treated with wide local excision followed by chemoradiation. We discuss the use of chemoradiation for this patient and review the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 13 publications
1
33
1
3
Order By: Relevance
“…Additionally, current strategies for cancer treatment vary, including surgery, chemotherapy, radiation therapy, and palliative care, among which radiotherapy and chemotherapy are more wildly used in the therapy of human cancer [5,6]. A large number of studies showed that the use of CRT, which is the combination of radiotherapy and chemotherapy is well described for cancer treatment [7,8]. Moreover, a large number of previous studies also revealed that some intrinsic genetic factors have significant influence on the prognosis of CRT [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, current strategies for cancer treatment vary, including surgery, chemotherapy, radiation therapy, and palliative care, among which radiotherapy and chemotherapy are more wildly used in the therapy of human cancer [5,6]. A large number of studies showed that the use of CRT, which is the combination of radiotherapy and chemotherapy is well described for cancer treatment [7,8]. Moreover, a large number of previous studies also revealed that some intrinsic genetic factors have significant influence on the prognosis of CRT [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These tumors are reported to occur in several organs, including nasopharynx, 3 salivary glands, 4 lungs, 5,6 and stomach, 7 and also have been uncommonly reported in trachea, 8 lacrimal glands, 9 ureters, 10 urinary bladder, 11,12 uterine cervix, 13 vagina, 14 ovaries, 15 breast, 16 soft tissue, 17 and skin. 18 Epstein-Barr virus (EBV) has been shown to be strongly associated with LELCs of the nasopharynx, 19 stomach, 20 salivary glands, 4 lungs, 5,6 and thymus 21 in the form of integration of the viral genome in the tumor cell nuclei. However, this association has not been shown in LELCs of the urinary bladder, 11 uterine cervix, 22,23 or skin.…”
mentioning
confidence: 99%
“…DLBK en sık baş-boyun bölgesinde görülür ve olguların %90'ında yüz yerleşimi bildirilmiştir. Tümör gövde ve çok nadiren ekstremitelerde de ortaya çıkabilir 6,7 . Literatürde tam yeri belirtilmeksizin 2 hastada kolda yerleşen lezyon bildirilmiştir 1 .…”
Section: Discussionunclassified
“…DLBK'nin klinik özellikleri tipik olmadığından, tanı oldukça zordur. Genellikle 0,4-4,5 cm arası değişen çaplarda, deri renginde veya kırmızı, sert soliter papül, nodül veya plak şeklinde ortaya çıkar 7 . Sıklıkla, aylar yıllar içinde büyüyen asemptomatik lezyon öyküsü bulunur.…”
Section: Discussionunclassified
See 1 more Smart Citation